1985
DOI: 10.1002/ps.2780160310
|View full text |Cite
|
Sign up to set email alerts
|

The resistance to eighteen toxicants of a strain of Musca domestica L. collected from a farm in England

Abstract: A sample of houseflies initially collected from a pig farm and found to be resistant to bendiocarb, DDT, gamma‐HCH, pyrethrins + piperonyl butoxide (PB), tetrachlorvinphos and trichlorfon, was tested for resistance to knockdown by other toxicants. At the KD50 response level, resistance factors were obtained for: permethrin (× 141), deltamethrin (×96), bioresmethrin + PB (×37), resmethrin + PB (×33), fenitrothion (×94), bromophos (×58), iodofenphos (×42), pirimiphos‐methyl (×30), dichlorvos (×22), dimethoate (×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1987
1987
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…The continued application of contact insecticides for control of the housefly, Musca domestica L. (Diptera: Muscidae), in intensive animal rearing units has led to the widespread development of resistance ( Chapman 1985; Chapman & Morgan 1992; Chapman et al . 1993 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The continued application of contact insecticides for control of the housefly, Musca domestica L. (Diptera: Muscidae), in intensive animal rearing units has led to the widespread development of resistance ( Chapman 1985; Chapman & Morgan 1992; Chapman et al . 1993 ).…”
Section: Introductionmentioning
confidence: 99%
“…The continued application of contact insecticides for control of the house¯y, Musca domestica L. (Diptera: Muscidae), in intensive animal rearing units has led to the widespread development of resistance (Chapman, 1985;Chapman & Morgan, 1992;Chapman et al, 1993). Due to the decreasing ef®ciency of contact insecticides, many U.K. farmers have come to rely on the use of toxic baits for M. domestica control, often applied to localized targets (Barson, 1987;Freeman & Pinniger, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Reliance on contact insecticides in intensive animal rearing units has led to the development of widespread resistance in many populations of Musca domestica L. (Diptera: Muscidae) (Chapman, 1985;Chapman & Morgan, 1992;Chapman et al, 1993). Control failure associated with persistent application of contact insecticides has resulted in an increase in the use of baited targets on many UK poultry farms (Barson, 1987;Freeman & Pinniger, 1992; J. W. Chapman, unpubl.…”
Section: Introductionmentioning
confidence: 99%
“…Two strains of M.dornestica were used; the Cooper susceptible strain which has been in continuous culture at the Slough Laboratory since 1979. and a multi-insecticide-resistant strain (G) which was collected from a pig farm in Suffolk during 1980. The level of methomyl resistance to strain G (determined by topical application) was x5.X at the KDvi value (Chapman, 1985). The resistance spectrum of strain G is reported by Chapman (1985).…”
Section: Houstfl? Struinsmentioning
confidence: 95%
“…The development of widespread resistance in houseflies to most of the insecticides currently used for their control in intensive animal units (Chapman & Lloyd, 1981;Chapman, 1984Chapman, , 1985 has led to a need to modify current control strategies. This was also emphasized by Denholm et al (1985) who demonstrated that the development and spread of resistance can be prevented by control measures based on a good understanding of housefly population dynamics.…”
Section: Introductionmentioning
confidence: 99%